FRASA VERBAL BAHASA MADURA - Iqbal Nurul Azhar (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2012)
The small amount ofreferencesrelated to Madurese language studies inspires the writer to present this article. This articlestudies Madurese language. which is percieved from a very specificcontext; syntacticphrasal context.From theresults of the study, it isfoundthat Madurese verbs vary in forms. Verbalphrasescan be categorized intothreebasedon thepresence or the absence ofnounswithin the structures, those are;transitive, intransitive, andditransitive verbal phrases. Basedon the complexity of the structures, verbalphrasescan be dividedinto two, those aresimplexandcomplex. Based on theposition ofheadconstituentsandattributes constituents, verbalphrasescan be dividedinto four, namelycoordinative verbalphrase,modificative verbalphrases, predicative verbalphrases, andcomplementative verbal phrases.The existence ofthis article isexpected to be amoraleboosterto linguistic researchers,tobeeven hardertocarry outmore researchrelated to Madurese language.